The Urgency of Compliance Audit 5.0 Through an Approach to Personal Data Protection Law: Pentingnya Audit Kepatuhan 5.0 Melalui Pendekatan terhadap Undang-Undang Perlindungan Data Pribadi - Frendika Suda Utama; Irma Dwi Yulistyani (Faculty of Law Hang Tuah University, 2026)
Datacrime is increasing massively and collectively in the era of Society 5.0. The era of data digitization has given rise to advances in information technology that affect all aspects of human life. The victims not only suffered material losses, but also immaterial. In Indonesia, there are not only cases of crimes against personal data in the financial sector (theft of customer data), but also in the public service sector, namely the leakage of voter data from the Indonesian Election Commission. This study aims to provide a comprehensive picture of personal data crimes, including descriptions of modus operandi and of how compliance audits are conducted from a personal data protection law perspective. The researcher used normative legal research, with a case approach, to explore the series of crimes and to unravel the ratio decidendi of the court's decision. This article also uses a conceptual approach, namely the perspective of Lex Specialist Data, and the regulation of digital data privacy. The technical regulation of data privacy legal aspects in the legal compliance audit aligns with the strengthening of personal data protection laws. The idea of a legal compliance audit through a personal data protection approach helps prevent and even mitigate the risk of data privacy crimes.